2017
DOI: 10.1093/mnras/stx2514
|View full text |Cite
|
Sign up to set email alerts
|

The VMC survey – XXVI. Structure of the Small Magellanic Cloud from RR Lyrae stars

Abstract: We present results from the analysis of 2997 fundamental mode RR Lyrae variables located in the Small Magellanic Cloud (SMC). For these objects near-infrared timeseries photometry from the VISTA survey of the Magellanic Clouds system (VMC) and visual light curves from the OGLE IV survey are available. In this study the multi-epoch K s -band VMC photometry was used for the first time to derive intensityaveraged magnitudes of the SMC RR Lyrae stars. We determined individual distances to the RR Lyrae stars from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 63 publications
10
84
0
Order By: Relevance
“…This was already hinted at by , briefly mentioned in Belokurov & Erkal (2019, fig. 3 where the gradient in the proper motions is evident) and implied by the smaller distance measured for the Eastern regions of the SMC (Subramanian & Subramaniam 2012;Deb et al 2015;Ripepi et al 2017;Muraveva et al 2018) as they are being pulled towards the LMC and thus closer to us. This last point is corroborated by the gradient seen in Fig.…”
Section: Tidal Disruption Of the Smcmentioning
confidence: 84%
“…This was already hinted at by , briefly mentioned in Belokurov & Erkal (2019, fig. 3 where the gradient in the proper motions is evident) and implied by the smaller distance measured for the Eastern regions of the SMC (Subramanian & Subramaniam 2012;Deb et al 2015;Ripepi et al 2017;Muraveva et al 2018) as they are being pulled towards the LMC and thus closer to us. This last point is corroborated by the gradient seen in Fig.…”
Section: Tidal Disruption Of the Smcmentioning
confidence: 84%
“…Ripepi et al (2017) also found that young and old Cepheids have different geometric distributions in the SMC. They observed that closer Cepheids are preferentially distributed in the eastern regions of the SMC which are off-centred in the direction of LMC owing to the tidal interaction between the two clouds (Muraveva et al 2018).…”
Section: Spatio-temporal Distributionmentioning
confidence: 99%
“…This repeated interaction between LMC and gas-rich SMC lead to episodic star formations in these two dwarf galaxies which are locked in tidal interaction. It is believed that the Magellanic Bridge and the Magellanic Stream might have formed due to such interactions in the past between the two segments of the MCs (Besla et al 2010;Muraveva et al 2018). As a consequence of these frequent encounters, the tidal stripping of stars and gas/material from the gaseous disk takes place in the Magellanic System.…”
Section: Age Distributionmentioning
confidence: 99%
“…Coppola et al 2011;Sollima et al 2006;Braga et al 2015), and in nearby galaxies (e.g. Moretti et al 2014;Karczmarek et al 2015;Muraveva et al 2018a).…”
Section: Introductionmentioning
confidence: 99%